Available transfer capability evaluation in electricity-dominated integrated hybrid energy systems with uncertain wind power: An interval optimization solution. (15th May 2022) - Jiang, Tao; Li, Xue; Kou, Xiao; Zhang, Rufeng; Tian, Guoda; Li, Fangxing
Highlights: An interval ATC evaluation model of IHES is developed. Wind power uncertainty is addressed by interval optimization. Strong duality theory and big-M algorithm are used to accelerate computational efficiency. Infulence of interdependenc in IHES on ATC is revealed. Abstract: Available transfer capability (ATC) is widely used in the deregulated electricity market to ensure secure and reliable power trading among market participants. However, most conventional ATC calculation methods do not fully consider the impacts of renewable energy integration and the close interdependency among electricity, natural gas, and district heating networks. To overcome these challenges, this work evaluates the ATC in an electricity-gas-heating integrated hybrid energy system (IHES) in a more practical manner by considering renewable energy uncertainties. In the proposed approach, the detailed models of electricity, natural gas, and district heating infrastructures are provided and their operational constraints are fully respected. To reduce input data requirements, the wind power uncertainty is modeled as interval bounds instead of detailed probability distribution functions (PDFs). Consequently, this interval optimization-based ATC model is converted to two sub-problems to solve the lower and upper boundaries of the objective function value. The proposed approach provides a quantitative approach to numerically calculate the impact on ATC from various components in an IHES. Simulation results on the IHES 5–7-6 and the IHES 118–96-6 + 32 systems validate its effectiveness.